2007
DOI: 10.1002/jez.b.21207
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of correlation and covariation of anthropoid distal forelimb segments correspond to Hoxd expression territories

Abstract: Anthropoids in general and hominoids in particular exhibit differential adaptations in forearm and digital skeletal proportions to a diverse array of locomotor modes. Hox genes act as selector genes with spatially regulated expression patterns during development. Their expression in the forelimb appears to define modules that specify differential skeletal growth. Here we explore forelimb skeletal proportions in a large sample of anthropoids from a background provided by Hoxd expression patterns in late-stage m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 71 publications
(31 reference statements)
4
62
0
Order By: Relevance
“…The bone in the "growing end" of the bone is therefore developmentally younger than the bone at the midshaft. The similar growth behavior of the knee epiphyses is largely a consequence of their origin within the same HOX territory and accounts for the marked stability of the crural index (femur/tibia) in the hindlimb but a much more varied brachial index in the forelimb, where the primary growth plates do not share a territory [45]. In our study this same pattern is revealed by the higher densities of haversian structures at midshaft.…”
Section: Discussionsupporting
confidence: 80%
“…The bone in the "growing end" of the bone is therefore developmentally younger than the bone at the midshaft. The similar growth behavior of the knee epiphyses is largely a consequence of their origin within the same HOX territory and accounts for the marked stability of the crural index (femur/tibia) in the hindlimb but a much more varied brachial index in the forelimb, where the primary growth plates do not share a territory [45]. In our study this same pattern is revealed by the higher densities of haversian structures at midshaft.…”
Section: Discussionsupporting
confidence: 80%
“…The resulting dose of HOXA and HOXD proteins is thus higher in developing digits 2-5 than in digit I, which will impact on the future morphologies, Hox genes being involved in the control of cell proliferation and digit patterning. This difference between digit I and the others suggests a regulatory explanation for the existence of two developmental modules underlying the evolution of anthropoid distal forelimbs (Reno et al 2007).…”
Section: The Ontogeny Of Mammalian Thumbness; a Dosage Effect Linked mentioning
confidence: 87%
“…32 Studies of how these Hox master genes control growth-affecting target genes may eventually reveal how anthropoids sculpted an opposable thumb from an ordinary digit. 21 Mutations that alter the Hox code can apparently reverse that sculpting, that is, they can convert a thumb back into an ordinary finger. Triphalangeal thumbs occur occasionally, but do not typically entail any loss of the muscles for opposability.…”
Section: The Homeobox Epiphanymentioning
confidence: 99%
“…17 If Shh malfunctions, then babies are born with a cyclops deformity, in which the two eyes merge at the midline, 18 and an ''all thumbs'' anomaly, in which all the fingers look like thumbs. 19 Both of these phenotypes are relevant to anthropology because interocular distances 20 and thumb lengths 21 figured prominently in primate evolution as adaptations, respectively, for depth perception and object manipulation. Incremental mutations in Shh pathways may have helped steer these organs in those directions.…”
Section: The Morphogen Epiphanymentioning
confidence: 99%